Clitocybin A, a Novel Isoindolinone, From the Mushroom Clitocybe aurantiaca, Inhibits Cell Proliferation Through G1 Phase Arrest by Regulating the PI3K/Akt Cascade in Vascular Smooth Muscle Cells - Kyu-Dong Yoo; Eun-Seok Park; Yong Lim; Shin-Il Kang; Su-Hyang Yoo; Ha-Hee Won; Young-Hee Kim; Ick-Dong Yoo; Hwan-Soo Yoo; Jin Tae Hong; Yeo-Pyo Yun (Elsevier, 2012)
Abnormal proliferation of vascular smooth muscle cells (VSMCs) plays an essential role in the pathogenesis of vascular diseases, such as atherosclerosis, hypertension, and restenosis. Clitocybin A, a novel isoindolinone, isolated from the culture broth of mushroom Clitocybe aurantiaca has been reported to possess free radical scavenging activity. However, the antiproliferative effects of clitocybin A on VSMCs are unknown. In the present study, we investigated the effect of clitocybin A on platelet-derived growth factor (PDGF)-BB-induced proliferation of VSMCs and examined the molecular basis of the underlying mechanism. Clitocybin A inhibited DNA synthesis and cell proliferation. In accordance with these findings, clitocybin A blocked the PDGF-BB-inducible progression through G0/G1 to S phase of the cell cycle in synchronized cells and decreased the expression of cyclin-dependent kinase (CDK) 2, CDK4, cyclin D1, cyclin E, and proliferative cell nuclear antigen. In addition, clitocybin A inhibited the PDGF-BB-induced phosphorylation of phosphatidylinositol 3 kinase (PI3K) / Akt kinase. However, clitocybin A did not change the expression levels of extracellular signal-related kinase (ERK) 1/2, phospholipase C-γ1, and PDGF-Rβ phosphorylation. These results indicate that clitocybin A may inhibit VSMCs proliferation through G1 phase arrest by regulating the PI3K/Akt pathway. Keywords:: clitocybin A, vascular smooth muscle cell, platelet-derived growth factor (PDGF)-BB, PI3K/Akt pathway